ACTUALIZATION OF STUDENT’S SOCIAL RESPONSIBILITY IN EFFORTS TO STRENGTHEN CIVIC ENGAGEMENT (Case Study at Student Association of Civic Education in Faculty of Teachers Training and Education, Lambung Mangkurat University) - Wardiani Hiliadi , Suwarma Al Muchtar (Al-Mabsut: Jurnal Studi Islam dan Sosial, 2017)
ABSTRACT; This study examines the value development of social responsibility owned by the students of civic education, Faculty of Teacher Training and Education (FKIP) in University of Lambung Mangkurat, as an effort of social engagement of students in the form of social service as one of the work programs of the Civic Education Student Association, University of Lambung Mangkurat. The aims of this study, among others; 1) Assess the social work activities of "Civic Education Makes Work" which is believed to develop the value of social responsibility in order to strengthen the involvement of citizens, starting from the assessment of the development reality of the social responsibility of the students in order to strengthen the involvement of citizens in Civic Education FKIP, University of Lambung Mangkurat. 2) Reviewed the implementation process of social work "Civic Education Makes Work" which has effective stages to develop the value of social responsibility in an effort to strengthen the involvement of citizens. 3) Assessing the impact and benefit of social work program of " Civic Education Makes Work" by the students of Civic Education FKIP University of Lambung Mangkurat as the value development of social responsibility in order to strengthen the involvement of citizens using qualitative-naturalistic approach and the research location is in FKIP University of Lambung Mangkurat and SDN Sungai Pinang Baru 2 in Sungai Tabuk District. The results of this study found some findings that there is a gap between conceptual understanding and practice, the involvement of civic education students is still at the level of conventional moral awareness, through the program of social work activities "Civic Education Makes Work" civic education students in FKIP ULM can develop the value of social responsibility as a whole, because the program can directly involve students to participate and engage in societies deemed to face social problems. The social work of "Civic Education Makes Work" has succeeded in actualizing the values of characters such as honest, independent, love of the homeland, environmental care, social care, social solidarity, mutual cooperation and responsibility from the relgius value of "faith and piety" as the basis for the development of citizen participation and involvement in developing the value of social responsibility, in addition to many local wisdom values such as, baiman, bauntung, batuah and baadab, kayuh baimbai , samuak saliur and haram manyarah, waja sampai kaputing. The development of the social responsibility value of "Civic Education Makes Work" is based on the problems that grow and develop in the community so that the benefits and impacts of these activities can be felt by students, teachers in SDN Sungai Pinang Baru 2 and the community. In addition, the sense of social responsibility of students based on honest values, independent, love of the homeland, environmental care, social care, mutual assistance and faith and piety-based responsibilities are actualized in a concrete manner in the form of assistance needed by students, teachers in SDN Sungai Pinang Baru 2 and surrounding communities.